SHM_415538_HST_3D Hollow Edge Stone Axe - Lernestål, Erik; Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a hollow edge stone axe from the Swedish Middle Neolithic. Originally collected in Skåne, it is now held in the collections of the National Historical Museums in Stockholm, Sweden

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=673

Link to Sök I Samlingarna

https://samlingar.shm.se/object/D90F222A-EAD3-4A0A-AF38-B2281FD6C1CC
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Dynamic Collections; Swedish Middle Neolithic; Archaeology/history; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi